PENGARUH CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSET (ROA), LOAN TO DEPOSIT RATIO (LDR) TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN (BUMN) YANG TERDAFTAR di BURSA EFEK INDONESIA (PERIODE 2011-2020) - Anggun Novita Sihite; Sugiyono Sugiyono (Journal of Fundamental Management (JFM), 2023)
This study aims to determine the "Effect of Capital Adequacy Ratio (CAR), Return on Assets (ROA) and Loan to Deposit Ratio (LDR) on Stock Prices of Banking Companies (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2011-2020. The sampling technique used a saturated sample using 4 state-owned banks. The data analysis used is panel data regression analysis with the help of Software Eviews 12. Based on the results of the partial study, it shows that CAR has a positive and significant effect on stock prices, ROA has no effect, and LDR has a positive and significant effect on stock prices.